Acacia mangium Willd: Ecology and silviculture in Vietnam - Chaw, C.S.; Mitlöhner, Ralph (Center for International Forestry Research, 2011)
This manual summarises information on the ecology and silviculture of the species Acacia mangium Willd, with an emphasis on Vietnam. It also encompasses growth and yield data from published sources, as well as collected from sites under smallholder industrial plantations in Phu Tho Province, Vietnam. This manual is 1 of 5 that guide smallholder tree planting of 5 selected tree species in Vietnam. The other 4 species are: Acacia hybrid, Cinnamomum parthenoxylon (Jack) Meisn, Erythrophloeum fordii Oliver and Eucalyptus urophylla S.T. Blake. The Government of Vietnam is carrying out a large-scale ‘reforestation’ programme, with the aim of improving local livelihood security, environmental sustainability and industrial wood supply. Smallholders are involved in plantation timber production through various schemes. Generally, these reforestation efforts have been effective, even though smallholders often lack the appropriate technical knowledge and management skills. Consequently, the quality and quantity of wood products may be suboptimal. The productivity of smallholder plantations can be improved by enhancing smallholders’ management knowledge and skills, including species selection (site matching), silvicultural management to produce high quality products, and pest and disease management.